Acid-base amphoteric iron-sulfur hybrid flow battery and preparation method thereof
By adopting a three-chamber design and polysulfide ion adsorption material in the flow battery, the problem of low electrochemical reaction speed of polysulfide negative electrode active substances is solved, and efficient electrochemical reactions and battery stability are achieved.
Patent Information
- Application Number
- CN202410664799.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-27
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-05-27
AI Technical Summary
The electrochemical reaction speed of polysulfides as negative electrode active substances is low, and polysulfide ions are prone to pass through the ion exchange membrane, resulting in a decrease in battery life and a difference in acid and alkalinity of positive and negative electrodes.
The three-chamber design of acid-base amphiphilic iron-sulfur hybrid flow battery is adopted, and the positive and negative electrodes and the intermediate chamber are separated by anion and cation exchange membranes. The activated carbon cloth of polysulfide ion adsorption material is added to the intermediate chamber to prevent the polysulfide ions from entering. Positive pole room.
It improves the electrochemical reaction speed, enhances the stability and service life of the battery, and achieves high power density and low cost battery performance.
Smart Images

Figure CN118412509B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of liquid flow batteries, and in particular relates to an acid-base amphoteric iron-sulfur hybrid liquid flow battery and a preparation method thereof. Background Art
[0002] Redox flow battery is a secondary battery that uses the redox reaction of electrochemically active substances dissolved in the electrolyte to store energy. With the rapid development of renewable energy such as wind and solar power, renewable energy with large fluctuations due to changes in the natural environment will have a huge impact on the stable operation of the power grid. In order to overcome these shortcomings, configuring an energy storage system is an important solution. Among them, flow batteries have attracted much attention for their flexible design, safety, fast response speed, decoupling of power and capacity, long service life, and low maintenance costs. They are particularly suitable for large-scale and long-term energy storage. As one of the core materials of flow batteries, electrolyte is a solution in which electrochemically active materials are dissolved and can undergo redox reactions quickly. Different types of flow batteries are formed according to the type of redox couple used. The redox flow batteries developed so far include: all-vanadium flow battery, iron / chromium flow battery, zinc / bromine flow battery, iron / sulfur flow battery, all-iron flow battery, organic flow battery, etc. In particular, all-vanadium flow batteries, because both the positive and negative electrolytes are vanadium ions of different valence states, there is no cross-membrane cross-permeation pollution, and it also overcomes the problem of hydrogen evolution at the negative electrode of iron / chromium flow batteries, and it was the first to be commercially applied. However, the limited amount of vanadium resources, high prices, and high production costs of electrolytes have limited its large-scale application. Organic flow batteries are still in the research and development stage due to unfavorable factors such as the complex synthesis of active materials, low solubility in water, low energy density, and poor chemical stability.
[0003] Generally, a flow battery consists of a stack unit, an electrolyte, an electrolyte storage and delivery unit, and a management and control unit. The stack unit consists of a positive and negative electrode chamber, an electrode, and an ion exchange membrane, which separates the positive / negative electrode chambers. In order for flow batteries to meet the requirements of large-scale commercial applications, the key is to develop redox pairs with a wide range of sources, low prices, good stability, high electrochemical activity, and high solubility. Among them, iron / sulfur flow batteries use different valence compounds of iron and polysulfides as positive and negative electrode active substances, respectively. Both iron and sulfur are abundant, low-priced, and non-toxic. Since polysulfides can only exist stably under alkaline conditions, usually the positive electrode active substances paired with polysulfides are ferrocyanate and ferrocyanate. The electrode pair composed of ferrocyanate and ferrocyanate has low solubility, poor chemical stability, and relatively high price, and low potential (0.51VSHE). While Fe 3+ / Fe 2+The raw materials of redox couples are very abundant, low cost, high electrochemical activity, moderate potential (0.77VSHE), and deep charge and discharge will not release oxygen, making them ideal positive electrode active materials. However, iron compounds are easily hydrolyzed to form insoluble hydroxides at high pH values, so iron-based electrolytes are usually only used under acidic conditions. Polysulfides as negative electrode active materials can obtain lower electrode potentials (-0.45V), high solubility, up to 8M / L, and high energy density.
[0004] Fe 3+ / Fe 2+ and polysulfide as positive and negative electrode active materials, respectively, can achieve high power density, low cost and large-scale application. However, due to the different acidity and alkalinity of the positive and negative electrode electrolytes, the H + and OH - Ions are neutralized across the membrane, causing the battery to fail quickly. Since the electrochemical window of water is only 1.23V, choosing suitable acid-base conditions and effectively controlling oxygen evolution at the positive electrode and hydrogen evolution at the negative electrode are the keys to obtaining a large battery voltage and a long service life. Polysulfides have a high overpotential on carbon felt electrodes, a slow electrochemical reaction rate, and low energy efficiency. Moreover, polysulfide ions easily pass through the ion exchange membrane to react with the positive electrode active material to generate insoluble substances that cause the battery capacity to decay. Therefore, solving the problems of low electrochemical reaction rate when polysulfide is used as a negative electrode active material, easy passage of polysulfide ions through the ion exchange membrane to reduce battery life, and the difference in acidity and alkalinity between the positive and negative electrodes is the key to the commercial application of iron-sulfur liquid flow batteries. Summary of the invention
[0005] The object of the present invention is to provide an acid-base amphoteric iron-sulfur hybrid flow battery and a preparation method thereof, so as to solve the problem of low electrochemical reaction rate when polysulfide is used as negative electrode active material.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] An acid-base amphoteric iron-sulfur hybrid flow battery, comprising a positive electrode chamber and a negative electrode chamber, an intermediate chamber is provided between the positive electrode chamber and the negative electrode chamber, an anion exchange membrane is provided between the positive electrode chamber and the intermediate chamber, and a cation exchange membrane is provided between the intermediate chamber and the negative electrode chamber;
[0008] The positive electrode chamber is provided with a positive electrode electrolyte, the negative electrode chamber is provided with a negative electrode electrolyte; the intermediate chamber is provided with an intermediate chamber electrolyte;
[0009] The positive electrode redox couple of the iron-sulfur hybrid flow battery is Fe 3+ / Fe 2+ ;
[0010] The negative electrode redox couple of the iron-sulfur hybrid flow battery is S2 2- / S4 2- .
[0011] Positive electrode reaction:
[0012] ;
[0013] Negative electrode reaction:
[0014]
[0015] Where X represents the oxidized state of the organic molecule catalyst and H2X represents its reduced state.
[0016] When charged, the molecular catalyst X receives two electrons from the electrode and is reduced to reduced H2X. H2X has a strong reducing property and converts S4 2- Restore to S2 2- , which is oxidized to the oxidized active substance X. The above process is repeated until S4 2- Restore all to S2 2- Catalyst X should have a fast electroreduction reaction rate and fast reduction of S4 2- The potential should be lower than S4 2- The potential is -0.45VSHE, preferably between -0.55 and -0.8V, and it has high stability and high solubility in a strong alkaline environment.
[0017] Furthermore, the positive electrode electrolyte includes a positive electrode active material, and the positive electrode active material is an inorganic salt of iron or an organic acid salt of iron;
[0018] The negative electrode electrolyte includes a negative electrode active material, and the negative electrode active material is polysulfide.
[0019] Further, the inorganic iron salt includes one of Fe2(SO3)3, FeSO4, FeCl3, FeCl2 and hydrates thereof, and the concentration of the inorganic iron salt in the positive electrode electrolyte is 5-6 mol / L;
[0020] The organic iron salt includes one of glycine iron salt, citric acid iron salt, malic acid iron salt, tartaric acid iron salt, gluconic acid iron salt and glucaric acid iron salt, and the concentration of the organic iron salt in the positive electrode electrolyte is 1-5 mol / L;
[0021] The polysulfide is potassium polysulfide or sodium polysulfide.
[0022] Furthermore, the positive electrode electrolyte includes a positive electrode auxiliary electrolyte and a pH adjuster;
[0023] The positive electrode auxiliary electrolyte is one or more of NaCl, KCl, Na2SO4, K2SO4, NH4Cl, (NH4)2SO4, with a concentration of 0.5-2 mol / L, preferably 1-1.5 mol / L;
[0024] The pH regulator includes an organic acid or an inorganic acid, and the pH regulator adjusts the pH value of the positive electrode electrolyte to ≤3; the organic acid includes citric acid, malic acid, tartaric acid, gluconic acid and diacid; the inorganic acid includes sulfuric acid or hydrochloric acid.
[0025] Furthermore, the negative electrode electrolyte includes a catalyst, a negative electrode auxiliary electrolyte and a strong base;
[0026] The concentration of the catalyst in the negative electrode electrolyte is 0.02-0.2 mol / L, the concentration of the negative electrode auxiliary electrolyte is 0.5-1.5 mol / L, and the concentration of the strong base is 0.5-2 mol / L.
[0027] Furthermore, the catalyst is an anthraquinone catalyst or a phenazine catalyst; the catalyst that can simultaneously meet the above conditions is an anthraquinone or phenazine derivative with a specific substituent. Increasing the concentration of the catalyst can speed up the reduction rate of the negative electrode electrolyte and improve the energy efficiency of the battery, but too high a concentration will increase the cost of the electrolyte.
[0028] The anthraquinone catalyst is a mixture of one or more of 2,6-dihydroxyanthraquinone and its derivatives, 1,3,5,7-tetrahydroxyanthraquinone and its derivatives, 1,2,3,5,6,7-hexahydroxyanthraquinone and its derivatives, and 2,6-diaminoanthraquinone and its derivatives in any proportion;
[0029] The phenazine catalyst is one or more of 2-hydroxyphenazine (PH), 7,8-dihydroxy-2-carboxylic acid phenazine (DHPC), and 7,8-dihydroxy-2-sulfonic acid phenazine (DHPS) mixed in any proportion;
[0030] The negative electrode auxiliary electrolyte is one or more of NaCl, KCl, Na2SO4, and K2SO4;
[0031] The strong base is NaOH or KOH.
[0032] Further, the electrolyte in the intermediate chamber electrolyte is composed of one or more of NaCl, KCl, Na2SO4, K2SO4, NH4Cl, (NH4)2SO4;
[0033] The concentration of the electrolyte in the intermediate chamber is >3 mol / L.
[0034] Furthermore, the anion exchange membrane uses a polymer composite membrane with a quaternary ammonium salt functional group. Since it only contacts the acidic electrolyte of the positive electrode and the neutral electrolyte of the intermediate chamber, the anion exchange membrane can be prevented from contacting a strong base and decomposing, which can effectively solve the stability problem of the membrane under strong alkaline conditions and improve the battery life. The cation exchange membrane uses a polymer composite membrane with a sulfonic acid group, which is required to have a high ion exchange capacity, a small water absorption expansion rate and a low membrane resistance.
[0035] Furthermore, the positive electrode chamber also includes a liquid flow frame, a positive electrode material, and a positive electrode bipolar plate.
[0036] The negative electrode chamber also includes a liquid flow frame, a negative electrode material, and a negative electrode bipolar plate.
[0037] The middle chamber also includes a liquid flow frame and a plastic net.
[0038] The acid-base amphoteric iron-sulfur hybrid flow battery also includes a positive electrode electrolyte storage tank, a negative electrode electrolyte storage tank and an intermediate chamber electrolyte storage tank.
[0039] A method for preparing an acid-base amphoteric iron-sulfur hybrid flow battery comprises the following steps:
[0040] Step S1: Under nitrogen protection, prepare the electrolyte:
[0041] 1) Prepare the positive electrode electrolyte and place the positive electrode electrolyte into the positive electrode electrolyte storage tank;
[0042] 2) Prepare the negative electrode electrolyte and place the negative electrode electrolyte into the negative electrode electrolyte storage tank;
[0043] 3) Prepare the intermediate chamber electrolyte and place the intermediate chamber electrolyte into the intermediate chamber electrolyte storage tank;
[0044] Step S2, assembling the flow battery.
[0045] Activated carbon cloth, a polysulfide ion adsorption material, is placed on the side of the intermediate chamber close to the cation exchange membrane to adsorb polysulfide ions passing through the cation exchange membrane, thereby effectively preventing polysulfide ions from entering the positive electrode chamber and reacting with the positive electrode active material, effectively solving the problem of battery capacity attenuation.
[0046] During battery testing, the positive electrode electrolyte is transferred between the positive electrode electrolyte storage tank and the positive electrode chamber by the positive electrode electrolyte pump, the negative electrode electrolyte is transferred between the negative electrode electrolyte storage tank and the negative electrode chamber by the negative electrode electrolyte pump, and the intermediate chamber electrolyte is transferred between the intermediate chamber electrolyte storage tank and the intermediate chamber by the intermediate chamber electrolyte pump.
[0047] Beneficial effects of the present invention:
[0048] The three-chamber design of the acid-base amphoteric iron-sulfur hybrid flow battery in the present invention can place the positive electrode electrolyte and the negative electrode electrolyte in an acid-base environment that is most conducive to the electrochemical reaction and chemical stability of the active material, thereby providing high electrolyte concentration, fast electrochemical reaction speed and high electrolyte stability. At the same time, under acidic conditions, the oxygen evolution potential of the positive electrode is as high as 1.23V, while Fe 3+ / Fe 2+ The potential of the electrode pair is only 0.77V, so there will be no oxygen evolution reaction. Similarly, under alkaline conditions at the negative electrode, the hydrogen evolution potential is lower than -0.8V, and with the overpotential, the negative electrode hydrogen evolution potential is below -1.0V, so there will be no hydrogen evolution problem. Moreover, due to the presence of the third chamber, the electrolyte transmembrane contamination is greatly alleviated, and the stability of the battery is greatly improved.
[0049] The acid-base amphoteric iron-sulfur hybrid flow battery provided by the present invention utilizes a highly active organic molecular catalyst combined with polysulfide, giving full play to the advantages of high electrochemical activity of the organic molecular catalyst, while taking advantage of the high solubility, low price and abundant sources of inorganic electroactive polysulfide. It can achieve a battery voltage of 1.25V, a high electrolyte energy density of more than 100wh / L, high electrochemical stability, and low battery cost, which is of great significance for large-scale energy storage.
[0050] The anion exchange membrane in the present invention uses a polymer composite membrane with a quaternary ammonium salt functional group. Since it only contacts the acid electrolyte of the positive electrode and the neutral electrolyte of the intermediate chamber, the anion exchange membrane can be prevented from contacting a strong base and decomposing, which can effectively solve the stability problem of the membrane under strong alkaline conditions and improve the battery life. The cation exchange membrane uses a polymer composite membrane with a sulfonic acid group, which is required to have a high ion exchange capacity, a small water absorption expansion rate and a low membrane resistance.
[0051] The electrolyte in the intermediate chamber of the present invention is used for conducting electricity, and at the same time, it transports anions to the positive electrode and cations to the negative electrode during charging, and receives anions from the positive electrode and cations from the negative electrode during discharging. It is composed of one or more of sodium chloride, potassium chloride, sodium sulfate, potassium sulfate, ammonium chloride, and ammonium sulfate, with a concentration of 3-5 mol / L, or a saturated solution. In the intermediate chamber, an activated carbon cloth, which is a polysulfide ion adsorption material, is placed on the side close to the cation exchange membrane to adsorb polysulfide ions passing through the cation exchange membrane, thereby effectively preventing polysulfide ions from entering the positive electrode chamber and reacting with the positive electrode active material, effectively solving the problem of battery capacity attenuation. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] The present invention will be further described below in conjunction with the accompanying drawings.
[0053] Figure 1 It is a schematic diagram of the structure of the iron-sulfur hybrid flow battery of the present invention.
[0054] In the figure: 1. Intermediate chamber electrolyte storage tank; 2. Positive electrode electrolyte storage tank; 3. Positive electrode chamber; 4. Anion exchange membrane; 5. Cation exchange membrane; 6. Negative electrode chamber; 7. Intermediate chamber; 8. Negative electrode electrolyte storage tank; 9. Positive electrode electrolyte pump; 10. Negative electrode electrolyte pump; 11. Intermediate chamber electrolyte pump. DETAILED DESCRIPTION
[0055] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0056] Example 1
[0057] (1) Positive electrode electrolyte preparation: Under N2 protection, ferrous chloride tetrahydrate, citric acid and potassium chloride were dissolved in deionized water to prepare a positive electrode electrolyte. The concentration of each component was:
[0058] Ferrous chloride: 3 mol / L;
[0059] Citric acid: 0.5 mol / L;
[0060] Potassium chloride: 1 mol / L.
[0061] (2) Negative electrode electrolyte preparation: Under N2 protection, potassium sulfide was dissolved in 1 mol / L KOH solution, and refined sulfur was added in an amount 3 times the molar amount of potassium sulfide. The solution was heated to 80 degrees and stirred for 10 hours until the sulfur was completely dissolved to obtain a reddish brown solution. The solution was then cooled to room temperature, and the catalyst 1,3,5,7-tetrahydroxyanthraquinone and the auxiliary electrolyte potassium chloride were added and stirred until completely dissolved to prepare the negative electrode electrolyte. The concentration of each component was:
[0062] Potassium tetrasulfide 1.5 mol / L;
[0063] 1,3,5,7-Tetrahydroxyanthraquinone 0.05 mol / L;
[0064] Potassium hydroxide 1 mol / L;
[0065] Potassium chloride 1mol / L.
[0066] (3) Intermediate chamber electrolyte: Under N2 protection, dissolve potassium chloride in deionized water to prepare a 4 mol / L solution.
[0067] (4) Acid-base amphoteric iron-sulfur hybrid flow battery assembly test:
[0068] See also Figure 1As shown, the acid-base amphoteric iron-sulfur hybrid flow battery in this embodiment includes a positive electrode chamber 3, an intermediate chamber 7 and a negative electrode chamber 6. An anion exchange membrane 4 is provided between the positive electrode chamber 3 and the intermediate chamber 7, and a cation exchange membrane 5 is provided between the intermediate chamber 7 and the negative electrode chamber 6. The positive electrode chamber 3 also includes a liquid flow frame, a positive electrode material, and a positive bipolar plate. The negative electrode chamber 6 also includes a liquid flow frame, a negative electrode material, and a negative bipolar plate. The intermediate chamber 7 also includes a liquid flow frame and a plastic net. The specific assembly process is as follows:
[0069] The positive bipolar plate, the liquid flow frame containing the positive electrode material, the anion exchange membrane 4, the liquid flow frame containing the plastic net, the cation exchange membrane 5, the liquid flow frame containing the negative electrode material, and the negative bipolar plate are stacked in sequence and sealed with 1 mm thick silicone rubber to obtain a battery unit;
[0070] The electrolyte flows in the liquid flow frame through a magnetic pump arranged on the liquid flow frame, and the liquid flow frame plays a supporting and guiding role in the liquid flow battery. An anion exchange membrane 4 is arranged between the positive electrode chamber 3 and the intermediate chamber 7, which only allows anions such as chloride ions and sulfate ions to pass through; a cation exchange membrane 5 is arranged between the intermediate chamber 7 and the negative electrode chamber 6, which only allows cations such as sodium ions and potassium ions to pass through.
[0071] Activated carbon cloth, a polysulfide ion adsorption material, is placed on one side of the intermediate chamber 7 close to the cation exchange membrane 5 to adsorb polysulfide ions passing through the cation exchange membrane 5, thereby effectively preventing polysulfide ions from entering the positive electrode chamber 3 and reacting with the positive electrode active material, effectively solving the problem of battery capacity attenuation.
[0072] During battery testing, the positive electrode electrolyte is transferred between the positive electrode electrolyte storage tank 2 and the positive electrode chamber 3 by the positive electrode electrolyte pump 9, the negative electrode electrolyte is transferred between the negative electrode electrolyte storage tank 8 and the negative electrode chamber 6 by the negative electrode electrolyte pump 10, and the intermediate chamber electrolyte is transferred between the intermediate chamber electrolyte storage tank 1 and the intermediate chamber 7 by the intermediate chamber electrolyte pump 11.
[0073] Among them, anion / cation exchange membrane (standard homogeneous cation membrane CT-5 / standard homogeneous anion membrane ATG-10, Hangzhou Lanran Technology Co., Ltd.);
[0074] The positive and negative electrode materials are carbon felt and carbon plate; the active area of carbon felt is 5cmx5cm (25cm 2 ), the carbon felt is 5mm thick and compressed by 20%; a 2mm wide and 1mm deep flow channel is engraved on the carbon plate; a 1mm thick silicone rubber seal is used between the positive and negative plates of the battery and the liquid flow frame and membrane;
[0075] The charge and discharge test was carried out using Wuhan Blue Electric Battery Test System CT3002K, with an electrolyte flow rate of 50ml / min and a current density of 100mA / cm 2As a result, the single cell voltage was 1.25V, the coulombic efficiency was 99.4%, and the energy efficiency was 81.4%. No capacity decay was observed after 100 cycles, indicating that the flow battery and electrolyte have high energy density (80wh / L), high stability and high energy efficiency.
[0076] Example 2
[0077] (1) Positive electrolyte: Under N2 protection, dissolve ferrous chloride and citric acid in deionized water to prepare a positive electrolyte. The concentration of each component is:
[0078] Ferrous chloride 4 mol / L;
[0079] Citric acid: 0.6mol / L.
[0080] (2) Negative Electrolyte: A negative electrolyte was prepared according to the method in Example 1, except that the amount of 1,3,5,7-tetrahydroxyanthraquinone was doubled to prepare a negative electrolyte with the following component concentrations:
[0081] Potassium tetrasulfide 2.0 mol / L;
[0082] 1,3,5,7-Tetrahydroxyanthraquinone 0.1 mol / L;
[0083] Potassium hydroxide 1 mol / L;
[0084] Potassium chloride 1mol / L.
[0085] (3) Intermediate chamber electrolyte: Prepare a 4 mol / L potassium chloride solution under N2 protection.
[0086] (4) Battery test: The battery test system in Example 1 was used for testing, with an electrolyte flow rate of 60 ml / min and a current density of 100 mA / cm 2 The results show that the single cell voltage is 1.25V, the coulombic efficiency is 99.6%, the energy efficiency is 83.5%, there is no attenuation after 100 cycles, and the energy density is 108wh / L. This shows that 1,3,5,7-tetrahydroxyanthraquinone is an effective reduction catalyst for the polysulfide negative electrode active material, and the three-chamber flow battery constructed has high energy density, high stability and high energy efficiency.
[0087] Example 3
[0088] (1) Preparation of positive electrode electrolyte: Under N2 protection, ferrous chloride and malic acid were dissolved in deionized water to prepare positive electrode electrolyte. The concentration of each component was:
[0089] Ferrous chloride 4 mol / L;
[0090] Malic acid 0.5 mol / L.
[0091] (2) Preparation of negative electrode electrolyte: Under N2 protection, potassium sulfide was dissolved in 1 mol / L KOH solution, and refined sulfur was added in an amount 3 times the molar amount of potassium sulfide. The solution was heated to 80 degrees and stirred to react until the sulfur was completely dissolved to obtain a reddish brown solution. The solution was then cooled to room temperature, and the catalyst 2,3-dihydroxyphenazine and the auxiliary electrolyte potassium chloride were added and stirred until they were completely dissolved to prepare the negative electrode electrolyte. The concentration of each component was as follows:
[0092] Potassium tetrasulfide 2.0 mol / L;
[0093] 2,3-Dihydroxyphenazine 0.1 mol / L;
[0094] Potassium hydroxide 1 mol / L;
[0095] Potassium chloride 1mol / L.
[0096] (3) Intermediate chamber electrolyte: Under N2 protection, dissolve potassium chloride in deionized water to prepare a 5 mol / L solution.
[0097] (4) Battery test: The battery test system in Example 1 was used for testing, with an electrolyte flow rate of 60 ml / min and a current density of 60 mA / cm. The results showed that the single cell voltage was 1.25 V, the coulomb efficiency was 99.5%, the energy efficiency was 85.6%, and the energy density was 108 wh / L.
[0098] Comparative Example 1:
[0099] (1) Positive electrolyte: Under N2 protection, dissolve ferrous chloride and citric acid in deionized water to prepare a positive electrolyte. The concentration of each component is:
[0100] Ferrous chloride 3mol / L
[0101] Citric acid: 0.5 mol / L
[0102] Potassium chloride: 1 mol / L
[0103] (2) Negative Electrolyte: A negative electrolyte was prepared according to the method in Example 1, except that 1,3,5,7-tetrahydroxyanthraquinone was not added to prepare the negative electrolyte. The concentrations of the components were as follows:
[0104] Potassium tetrasulfide 1.5 mol / L
[0105] Potassium hydroxide 1mol / L
[0106] Potassium chloride 1 mol / L
[0107] (3) Intermediate chamber electrolyte: Prepare a 4 mol / L potassium chloride solution.
[0108] (4) Battery test: The battery test system in Example 1 was used for testing, with an electrolyte flow rate of 50 mL / min and a current density of 100 mA / cm 2 The results show that the single cell voltage is 1.25V, the coulombic efficiency is 87.2%, and the energy efficiency is 64.6%. This shows that without 1,3,5,7-tetrahydroxyanthraquinone as a reduction catalyst for the polysulfide negative electrode active material, the coulombic efficiency and energy efficiency are greatly reduced, indicating that the electrochemical activity of polysulfides on the carbon felt electrode is low, and the three-chamber flow battery cannot achieve high energy efficiency.
[0109] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0110] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. An acid-base amphoteric iron-sulfur hybrid flow battery, characterized in that: It comprises a positive electrode chamber and a negative electrode chamber, an intermediate chamber is arranged between the positive electrode chamber and the negative electrode chamber, an anion exchange membrane is arranged between the positive electrode chamber and the intermediate chamber, and a cation exchange membrane is arranged between the intermediate chamber and the negative electrode chamber; The positive electrode chamber is provided with a positive electrode electrolyte, the negative electrode chamber is provided with a negative electrode electrolyte; the intermediate chamber is provided with an intermediate chamber electrolyte; The positive electrode redox couple of the iron-sulfur hybrid flow battery is Fe 3+ / Fe 2+ ; The negative electrode redox couple of the iron-sulfur hybrid flow battery is S2 2- / S4 2- ; The negative electrode electrolyte includes a catalyst, a negative electrode auxiliary electrolyte and a strong base; The concentration of the catalyst in the negative electrode electrolyte is 0.02-0.2 mol / L, and the catalyst is an anthraquinone catalyst or a phenazine catalyst; The anthraquinone catalyst is a mixture of one or more of 2,6-dihydroxyanthraquinone and its derivatives, 1,3,5,7-tetrahydroxyanthraquinone and its derivatives, 1,2,3,5,6,7-hexahydroxyanthraquinone and its derivatives, and 2,6-diaminoanthraquinone and its derivatives in any proportion; The phenazine catalyst is one or more of 2-hydroxyphenazine, 7,8-dihydroxy-2-carboxylic acid phenazine, and 7,8-dihydroxy-2-sulfonic acid phenazine mixed in any proportion; The anion exchange membrane is a polymer composite membrane with quaternary ammonium salt functional groups; Activated carbon cloth, a polysulfide ion adsorption material, is placed on one side of the middle chamber close to the cation exchange membrane; The positive electrode electrolyte includes a positive electrode auxiliary electrolyte and a pH adjuster, and the pH adjuster includes an organic acid or an inorganic acid; The electrolyte in the intermediate chamber electrolyte is composed of one or more of NaCl, KCl, Na2SO4, K2SO4, NH4Cl, (NH4)2SO4.
2. The acid-base amphoteric iron-sulfur hybrid flow battery according to claim 1, characterized in that: The positive electrode electrolyte includes a positive electrode active material, and the positive electrode active material is an inorganic salt of iron or an organic acid salt of iron; The negative electrode electrolyte includes a negative electrode active material, and the negative electrode active material is polysulfide.
3. The acid-base amphoteric iron-sulfur hybrid flow battery according to claim 2, characterized in that: The inorganic iron salt includes one of Fe2(SO3)3, FeSO4, FeCl3, FeCl2 and hydrates thereof, and the concentration of the inorganic iron salt in the positive electrode electrolyte is 5-6 mol / L; The organic iron salt includes one of glycine iron salt, citric acid iron salt, malic acid iron salt, tartaric acid iron salt, gluconic acid iron salt and glucaric acid iron salt, and the concentration of the organic iron salt in the positive electrode electrolyte is 1-5 mol / L; The polysulfide is potassium polysulfide or sodium polysulfide.
4. The acid-base amphoteric iron-sulfur hybrid flow battery according to claim 1, characterized in that: The positive electrode auxiliary electrolyte is one or more of NaCl, KCl, Na2SO4, K2SO4, NH4Cl, (NH4)2SO4, with a concentration of 0.5-2 mol / L; The pH adjuster adjusts the pH value of the positive electrode electrolyte to ≤3; the organic acid includes citric acid, malic acid, tartaric acid, gluconic acid and diacid; the inorganic acid includes sulfuric acid or hydrochloric acid.
5. The acid-base amphoteric iron-sulfur hybrid flow battery according to claim 1, characterized in that: The concentration of the negative electrode auxiliary electrolyte is 0.5-1.5 mol / L, and the concentration of the strong base is 0.5-2 mol / L.
6. The acid-base amphoteric iron-sulfur hybrid flow battery according to claim 5, characterized in that: The negative electrode auxiliary electrolyte is one or more of NaCl, KCl, Na2SO4, and K2SO4; The strong base is NaOH or KOH.
7. The acid-base amphoteric iron-sulfur hybrid flow battery according to claim 1, characterized in that: The concentration of the electrolyte in the intermediate chamber is greater than 3 mol / L.
8. The method for preparing an acid-base amphoteric iron-sulfur hybrid flow battery according to claim 1, characterized in that: The steps include: Step S1: Under nitrogen protection, prepare the electrolyte: 1) Prepare the positive electrode electrolyte and place the positive electrode electrolyte into the positive electrode electrolyte storage tank; 2) Prepare the negative electrode electrolyte and place the negative electrode electrolyte into the negative electrode electrolyte storage tank; 3) Prepare the intermediate chamber electrolyte and place the intermediate chamber electrolyte into the intermediate chamber electrolyte storage tank; Step S2, assembling the flow battery.
Citation Information
Patent Citations
Lithium-sulfur battery with carbon fiber cloth as barrier layer
CN104900830A
Redox flow battery with electrolyte balancing and compatibility enabling features
US20200044267A1
Polysulfide-based aqueous redox flow battery with soluble organic catalyst
US20230307682A1